TERAPI ALBENDAZOLE PADA KASUS CUTANEOUS LARVA MIGRANS (CLM) DENGAN INFEKSI BAKTERI SEKUNDER - Suwito, Eva Aguswulandari; Hartati, Farida (Faculty of Medicine Universitas Mataram, 2021)
Cutaneous Larva Migrans (CLM) is caused by invasion of the hookworm larvae into the skin. In this case, we report a 32 – year- old male patient diagnosed with CLM and secondary bacterial infection. The patient was given oral albendazole 400mg, oral cefixime 100mg, combination oxytetrasiklin and gentamisin topical, combination oral albendazole 400mg with topical betametason valerat 0,1%, and oral cetirizine. The patient showed improvement of the skin lesions after 11 days of therapy.